2022
DOI: 10.3389/frsen.2022.878731
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Local Carbon Dioxide and Nitrogen Oxide Emissions From Space Using the Divergence Method: An Application to the Synthetic SMARTCARB Dataset

Abstract: Since the Paris Agreement was adopted in 2015, the role of space-based observations for monitoring anthropogenic greenhouse gas (GHG) emissions has increased. To meet the requirements for monitoring carbon dioxide (CO2) emissions, the European Copernicus programme is preparing a dedicated CO2 Monitoring (CO2M) satellite constellation that will provide CO2 and nitrogen dioxide (NO2) observations at 4 km2 resolution along a 250 km wide swath. In this paper, we adapt the recently developed divergence method to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…one year). Recently, Hakkarainen et al (2022) proposed an extension of the divergence method to CO 2 based on synthetic CO 2 observations that could also be applied to future satellite observations over areas with multiple point sources close to each other.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…one year). Recently, Hakkarainen et al (2022) proposed an extension of the divergence method to CO 2 based on synthetic CO 2 observations that could also be applied to future satellite observations over areas with multiple point sources close to each other.…”
Section: Discussionmentioning
confidence: 99%
“…Also, no plumes can be observed during persistently cloudy conditions or during night-time. This clear-sky bias will remain an issue for any emission estimation method based on passive remote sensing observations, including those methods based on temporal averaging (Hakkarainen et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the method has also been applied to other satellites such as GEMS NO 2 data (Xu et al, 2023). A study of its application to synthetic CO 2 data for the upcoming CO2M mission can be found in Hakkarainen et al (2022), which notes that a background and noise removal step must be applied to make the method robust for CO 2 data. Since its inception by Beirle et al (2019), notable improvements to the method include a different order of operations (differentiatethen-average instead of average-then-differentiate) as proposed in de Foy and Schauer (2022), computing the results on the satellite swaths themselves before remapping to a uniform grid as proposed in de Foy and Schauer (2022), skipping computations proportional to the wind divergence and adding a correction term proportional to the gradient of the topography as proposed in Sun (2022), and approximating the divergence operation using finite-difference stencils that can account for non-pixel-aligned transport as proposed in Sun (2022) and Veefkind et al (2023).…”
Section: Introductionmentioning
confidence: 99%
“…The SMARTCARB simulations were run with the COSMO-GHG model for a domain centred on Berlin and covering several neighbouring power plants (Jänschwalde, Lippendorf, Boxberg and others). The simulations were used to generate synthetic CO2M observations (Kuhlmann et al, 2020b) and to assess different plume detection and inversion methods (Kuhlmann et al, 2019a(Kuhlmann et al, , 2020a(Kuhlmann et al, , 2021Hakkarainen et al, 2022). The model fields consist of hourly data over one year with a spatial resolution of 0.01 • and sixty vertical layers from 0 to 24 km.…”
Section: Introductionmentioning
confidence: 99%